Studying the Old Testament : from tradition to canon - Ohler, Annemarie; Cairns, David, trans (Edinburgh : T & T Clark)
Translation of: Gattungen im AT
Includes bibliographies and indexes
Keywords: Bible. O.T. -- Criticism, interpretation, etc